Cropping With Slag to Address Soil, Environment, and Food Security - Das, Suvendu; Kim, Gil Won; Hwang, Hyun Young; Verma, Pankaj Prakash; Kim, Pil Joo (Frontiers in Microbiology, 2019)
The effective utilization of slag fertilizer in agriculture to neutralize soil acidity, improve crop productivity, mitigate greenhouse gas emissions, and stabilize heavy metals in contaminated soils turns it into a high value added product in sustainable agriculture. These effects could be due to the shift in microbial metabolism and/or modification of microbial habitats. At the system level, soil microorganisms play an integral role in virtually all ecosystem processes. There is a growing interest to reveal the underlying mechanisms of slag-microbe interactions and the contribution of soil biota to ecosystem functioning. In this perspective, we discuss the possible driving mechanisms of slag-microbe interactions in soil and how these slag-microbe interactions can affect crop yield, greenhouse gas emissions, soil carbon sequestration, and heavy metal stabilization in contaminated soils. In addition, we discuss the problems and environmental concerns in using slag in agriculture. Emphasis has been given for further research to validate the proposed mechanisms associated with slag-microbe interactions for increasing soil quality, crop productivity and mitigating environmental consequences. While evaluating the slag amendment effects on agriculture and environment, the potential risks, socio-economics, techno-economics and ethics should be assessed.